A SCALABLE SECURITY SERVICE FOR GEOGRAPHIC AD-HOC ROUTING - Karakehayov, Zdravko; Radev, Ivan (International Journal of Computing, 2014)
This paper describes a scalable security service for geographic ad-hoc routing. The routing protocol, REWARD, detects black hole attacks and organizes a distributed data base for suspicious nodes and areas. The algorithm utilizes two types of broadcast messages, MISS and SAMBA, to recruit nodes to act as security servers. Security servers keep records for detected black hole attacks and provide security services when forward packets. MISS-recruited security servers keep records for suspicious nodes and protect the network in the ID space. SAMBArecruited security servers keep records for suspicious areas and decline the network vulnerability in the physical space. REWARD has different levels of security which can be set according to the local conditions. In order to determine the effectiveness of REWARD we used ANTS, a simulation environment which models the traffic of wireless sensor networks.